Penentuan Key Performance Indicator Dengan Metode Balanced Scorecard - Rokhim, Muh (Department Industrial Engineering, University of Muhammadiyah Malang, 2017)
Balanced Score Card (BSC) is one of the management tools to manage the implementation of strategy, measure the performance beyond mere financials and to communicate the vision, strategy and performance to stakeholders. In this research, researcher will focus on cascading the Key Performance Indicator (KPI) with using the BSC methodology in the industrial Engineering Department at one of the tire manufacturing company located in Tangerang. This KPI will be a good tools to manage the performance of each engineers in the organization and to ensure align with the vision and strategy from the Top Management. Result of the KPI performance also will be an useful Performance Management tool for the ManagerÂ in order to give the yearly appraisal for each engineers in avoiding of the subjective way likes currently happened.